2024
DOI: 10.1111/geb.13828
|View full text |Cite
|
Sign up to set email alerts
|

A unified framework for partitioning the drivers of stability of ecological communities

Jules Segrestin,
Lars Götzenberger,
Enrique Valencia
et al.

Abstract: AimIdentifying the drivers of ecological stability is critical for ensuring the maintenance of ecosystem functioning and services, particularly in a changing world. Different ecological mechanisms by which biological communities stabilize ecosystem functions (i.e. “stabilizing effects”) have been proposed, yet with various theoretical expectations and debated conclusions. Here we propose a unified framework that aims at reconciling, and combining, different approaches to reliably test the strength of three sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This reveals a certain, although relatively weak, contribution of dominant species to overall community stability. The contribution of dominants to community stability has been further confirmed by the fact that the removal of the one most dominant species in the same locality (see Lepš et al, 2018), decreased the dominance and increased the averaging effect (Segrestin et al, 2024).…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…This reveals a certain, although relatively weak, contribution of dominant species to overall community stability. The contribution of dominants to community stability has been further confirmed by the fact that the removal of the one most dominant species in the same locality (see Lepš et al, 2018), decreased the dominance and increased the averaging effect (Segrestin et al, 2024).…”
Section: Discussionmentioning
confidence: 84%
“…We used the difference between the average species CV (CV e ) and abundance-weighted mean species CV ( CV) as a quantification of dominance effect (Segrestin et al, 2024;Thibaut & Connolly, 2013) and showed that the extent of variability attributable to differences in species abundance accounts for approximately 15% in more diverse communities. This reveals a certain, although relatively weak, contribution of dominant species to overall community stability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations